DIET AT EARLY STAGES OF CHILD'S DEVELOPMENT AND OPPORTUNITIES OF ITS PRACTICAL REALIZATION - O.A. Matalygina ("Paediatrician" Publishers LLC, 2010)
The article analyzes modern state of a problem of nutrition influence on formation of child's health in early periods of its development. Author compares different opportunities of optimization of fetus and breast-fed child.Key words: pregnant women, nursing mother, infants, nutrition.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):124-131)